Loss of the matrix metalloproteinase-10 causes premature features of aging in satellite cells - Bobadilla Muñoz, Miriam; Orbe, Josune; Abizanda, Gloria; Machado, Florencio J. D.; Vilas, Amaia; Ullate-Agote, Asier; Extramiana, Leire; Baraibar Churio, Arantxa; Aranguren, Xabier L.; Cantero, Gloria; Sáinz Amillo, Neira; Rodríguez, José Antonio; et al. (Frontiers in Cell and Developmental Biology, 2023)
Aged muscles accumulate satellite cells with a striking decline response to damage. Although intrinsic defects in satellite cells themselves are the major contributors to aging-associated stem cell dysfunction, increasing evidence suggests that changes in the muscle-stem cell local microenvironment also contribute to aging. Here, we demonstrate that loss of the matrix metalloproteinase-10 (MMP-10) in young mice alters the composition of the muscle extracellular matrix (ECM), and specifically disrupts the ECM of the satellite cell niche. This situation causes premature features of aging in the satellite cells, contributing to their functional decline and a predisposition to enter senescence under proliferative pressure. Similarly, reduction of MMP-10 levels in young satellite cells from wild type animals induces a senescence response, while addition of the protease delays this program. Significantly, the effect of MMP-10 on satellite cell aging can be extended to another context of muscle wasting, muscular dystrophy. Systemic treatment of mdx dystrophic mice with MMP-10 prevents the muscle deterioration phenotype and reduces cellular damage in the satellite cells, which are normally under replicative pressure. Most importantly, MMP-10 conserves its protective effect in the satellite cell-derived myoblasts isolated from a Duchenne muscular dystrophy patient by decreasing the accumulation of damaged DNA. Hence, MMP-10 provides a previously unrecognized therapeutic opportunity to delay satellite cell aging and overcome satellite cell dysfunction in dystrophic muscles.